1997
DOI: 10.1007/s004420050214
|View full text |Cite
|
Sign up to set email alerts
|

Litter dynamics in riverine mangrove forests in the Guayas River estuary, Ecuador

Abstract: The hypothesis that rates of litter turnover in mangroves are controlled by local geophysical processes such as tides has been studied at sites with mostly small tides (<1 m) and minor crab consumption of leaf litter. Our study describes litter dynamics of three riverine mangrove sites (M1, M2, M3), inhabited by the mangrove crab Ucides occidentalis, located in a macrotidal (>3 m) river-dominated tropical estuary in Ecuador (2.5°S latitude). There were statistical effects of site and depth on soil salinities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
1
19

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(126 citation statements)
references
References 35 publications
9
97
1
19
Order By: Relevance
“…Water soaking causes leaching of labile materials and promotes microbial activity both of which Table 4 The density of sediment infauna (macrobenthos) in the S. alba and R. mucronata treatments (Extracted from Bosire et al, 2004) increase decomposition rates (Tam et al, 1990;Ashton et al, 1999). Other than specific mangrove stand physical characteristics, differences in litter quality have also been found to be critical in influencing decay rates (Robertson, 1988;Steinke et al, 1990;Twilley et al, 1997). High tannin content is known to be aversive to detritivores and thus inhibit microbial activity (Steinke et al, 1990;Ashton et al, 1999), while nutritious leaf material with low C:N ratios have higher decay rates (Wieder and Lang, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water soaking causes leaching of labile materials and promotes microbial activity both of which Table 4 The density of sediment infauna (macrobenthos) in the S. alba and R. mucronata treatments (Extracted from Bosire et al, 2004) increase decomposition rates (Tam et al, 1990;Ashton et al, 1999). Other than specific mangrove stand physical characteristics, differences in litter quality have also been found to be critical in influencing decay rates (Robertson, 1988;Steinke et al, 1990;Twilley et al, 1997). High tannin content is known to be aversive to detritivores and thus inhibit microbial activity (Steinke et al, 1990;Ashton et al, 1999), while nutritious leaf material with low C:N ratios have higher decay rates (Wieder and Lang, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on mangrove litter degradation and concomitant nutrient dynamics have hitherto concentrated on differences among: tidal elevations (Twilley et al, 1986(Twilley et al, , 1997Mfilinge et al, 2002), species and seasons (Tam et al, 1990;Twilley et al, 1997;Woitchik et al, 1997;Mfilinge et al, 2002) and litter components (Steinke et al, 1983;Van der Valk and Attiwill, 1984;McKee and Faulkner, 2000). Specific stand management regimes, i.e., regulated exploitation versus excessive extractive pressure which leads to deforestation, and subsequent reforestation in areas where natural regeneration is impeded, do influence nutrient recycling (Ashton et al, 1999), Reforestation has been found to alter site physico-chemical conditions (McKee and Faulkner, 2000;Bosire et al, 2003) and is thus assumed to ultimately restore the functional importance of nutrient fluxes through it among other ecosystem functions.…”
Section: Introductionmentioning
confidence: 99%
“…Since leaves of both species were exposed to the same environmental conditions, so the differences in the decompo sition rates are probably due to the differences in the leaf morphology, texture and chemical Volume 4 | Number 1 | January | 2014 39 39 composition. Differences in leaf quantity are known to affect decomposition rates [5,21,36]. Different decay constant had been recorded for different mangroves species in different geographical location and in different regions (Table II), probably due to the differences in the nitrogen and tannin contents [6,13,35,37].…”
Section: Decomposition Of Mangroves Leavesmentioning
confidence: 99%
“…The fallen mangrove litter on the forest floor is decomposed by the bacterial action and other organisms, as well as acted upon by physical, chemical and biological processes [1][2][3][4][5][6], and generate a continuous source of nutrients in mangrove ecosystem [7][8][9][10]. These nutrients ions (most importantly the ammonium, nitrate, nitrites) are finally available for primary production and this in turn supports a wide variety of consumers [5][6][11][12]. The process of decomposition of mangrove leaves can be divided in three phases [3].…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of deforestation on mangrove fauna have not yet been documented in West Africa. The significant role of crabs as a engineer species starts to be recognized, but their ecological answers with respect to human pressures are poorly known compared to other aspects of their life such as diversity, distribution, sex ratio, ecological roles, feeding ecology, plant periodical migrations, physiological adaptations, domestic wastewater effects,… [22,23,24,25,26,27,28,29,30]. So, the aim of this study is to determine the impact of human pressures on mangrove crab biodiversity in Cameroon.…”
Section: Introductionmentioning
confidence: 99%